2010
DOI: 10.2298/abs1004119s
|View full text |Cite
|
Sign up to set email alerts
|

Classification of trees and tree species in Obrenovac “Mali park” by the elements of growth, vitality and ornamentalness

Abstract: The study was performed in Mali Park, in the town of Obrenovac. Our findings are based on the data obtained after direct measurements of elements of growth and the derived indicators of tree vitality and ornamentalness. Cluster analysis was applied to determine the relatively homogeneous groups of tree species. The results show that the group with the best functional characteristics includes Platanus acerifolia, Tilia grandifolia and Fraxinus ornus, and the group of species with inferior char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…As it has already been stated, besides trees, grass and weed are also allergenic species. The numerous authors (Stavretović et al 2006, Stavretović et al 2010aStavretović et al, 2010b, Stavretović et al 2011, Petrović et al 2013 have noted a significant presence of allergenic species of grass and weed on different types of urban green areas.…”
Section: Betula Pendulamentioning
confidence: 99%
“…As it has already been stated, besides trees, grass and weed are also allergenic species. The numerous authors (Stavretović et al 2006, Stavretović et al 2010aStavretović et al, 2010b, Stavretović et al 2011, Petrović et al 2013 have noted a significant presence of allergenic species of grass and weed on different types of urban green areas.…”
Section: Betula Pendulamentioning
confidence: 99%
“…For example, He used association rule analysis to explore the relationship between different urban growth patterns on urban vitality, and the results indicated that different forms of urban growth have different effects on urban vitality [36]. On the other hand, "growth" refers to the growth of urban trees [56,57]. These keywords also include "drought", "tree vitality", "vegetation", and "forest".…”
Section: Abstract Co-occurrence Analysis: Main Topic Distribution Andmentioning
confidence: 99%